MEMBACA CITRA KOTA SINGARAJA - NYOMAN GEDE SUARDANA (Jurnal Anala, 2012)
Singaraja town with its territory of 27,89 Km2 is a part of an administrative territory at Buleleng regency. Itâ€™s predicted that Singaraja town is the only one having an â€œurban designâ€. A territory has a meaning as a place of a city architecturally, and also itâ€™s set up by a space. Beside the existence of a Puri (castle), a traditional market, a harbor, China-town and the others, at Singaraja town is also available a lot of the Dutchâ€™s architectural heritage.A town image is a mental description of a city according to its societyâ€™s viewpoint approximate. Related to be an effort of keeping Singaraja town image that has an unique characteristic, so it needs taking care and preserving by conducting a conservation.Â Key word : the image-Singaraja town-conservation Â Â